Narrative Review: Expired Medicines in Public Health Services and Exploration of Causal Factors and Prevention Strategies - Cicillia Debora Melissa Sumardi; Diah Ayu Puspandari; Anna Wahyuni Widayanti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Although medications are essential to healthcare, the issue of expired medicines in public health institutions continues to be a significant obstacle. Various studies show high rates of expired medicines, such as in Jimma Zone (4.87%), Dire-Dawa (3.07%), Hadiya Zone (5.24%), and Arsi Zone (7.66%). The leading causes include delivery of drugs close to expiry, inaccurate quantity planning, weak stock management systems, and limited clinician involvement in the procurement process. Expired drugs cause economic losses, reduced healthcare quality, and environmental impacts. Objectives: to critically appraise, synthesize, and present available evidence on the possible causal factors associated with expired drugs, their impacts, and preventive mitigation or reduction strategy recommendations. Methods: Narrative literature review: content analysis. Results: The main factors leading to expired drugs include delivery of drugs close to the expiration date, inaccurate stock planning, weak inventory management systems, sudden changes in therapeutic protocols, and lack of clinician involvement in the drug procurement process. The impact of this problem is not only significant economic losses and increased waste disposal costs, but also a decrease in the quality of pharmaceutical services, potential environmental pollution, and a negative impact on the distribution of health budgets. Various strategies have been implemented, such as stock management training, the use of digital systems, and coordination among related units, which are expected to reduce the drug expiration rate. Conclusion: expired drugs remain a serious issue that requires collaborative efforts and innovation in the drug management system to achieve optimal budget efficiency and quality of health services.